Radiative properties of molybdenum sulfide and other transition metal dichalcogenides - Charron, Luc G (University of Ottawa (Canada), 2004)
Low temperature radiative properties of the layered transition metal dichalcogenides 2H-MoS2, 2H-WS2 and 2H-WSe 2 are investigated. Synthetically grown crystals of all three materials, natural 2H-MoS2 single crystals and several 2H-MoS2 and 2H-WS2 commercial powders are studied. Steady-state photoluminescence (PL) measurements performed on the samples reveal two distinct radiative regions in the near infrared. The first region consisting of several sharp lines is produced by bound excitons related to the halogen transport agent intercalated within the van der Waals gap of the layered compounds. The second weaker region, composed of a broad spectral band, originates from the radiative recombination between an intrinsic crystal lattice defect center and the valence band in the conditions of a strong electron-phonon coupling. Time decay analysis of the bound excitonic radiative transitions is performed with time-resolved and PL intensity ratio measurements. The spectral and temperature dependence of the total radiative emissions of all three compounds are described in the framework of a two-channel kinetic recombination model in thermal equilibrium conditions. A configuration coordinate diagram is also constructed for 2H-MoS 2. PL intensity measurements performed on the 2H-MoS2 and 2H-WS2 synthetic crystals reveal a sublinear PL dependence on excitation intensity. Finally a technique developed to intercalate halogen molecules in natural 2H-MoS2 single crystals is described.
Keywords: Physics, Radiation.